Additive Manufacturing of Polyether Ether Ketone – PEEK Parts with Surface Roughness Modification by a Laser Beam - Marcin KROLIKOWSKI; Damian PRZESTACKI; Tadeusz CHWALCZUK; Ewa SOBOLEWSKA; Malgorzata TOMASIK (Journal of Machine Engineering)
The physicochemical properties of polyether ether ketone (PEEK) allow to use this material for prosthetic restorations applied in implant prosthetics. So far, such attempts have been made in the technology of milling rough material solids of this polymer, but the surface quality was unsatisfactory. Therefore, the production of these materials by additive manufacturing techniques was proposed and an attempt was made to shape their surface using a laser. The possibilities of the method are determined in the paper and preliminary works related to the product surface shaping are presented. The process of making individual prosthetic restorations from the PEEK material by the additive method together with the technology of laser modification of the geometric structure of the material surface for applications in implant prosthetic treatment of patients is innovative and has not been used so far.